(untitled) (Eurasian Journal of Philology Science and Education, 2016)
This article analyzes the concept of «future» on a material product Alexiyevich «Chernobyl Prayer». The author of this article presents the results of observations of verbal incarnation of tokens «future». This article draws a parallel between the future prospects of the time imagined and hypothetical assumptions. The figure shows a representation of factual data analyzed concept in future semantics of language units. An illustrative material allowed the author to prove that the concept of «the future» in the product is passed through the future tense of verbs and implemented in the speech acts: prediction, assuming, threat. In conclusion, it highlights the temporal relationship, constitute a certain unity of the conceptual field.